Lessons in teaching computing in primary schools - Bird, James (Lessons in teaching., 2017)
Lesson planning and subject knowledge go hand in hand in this exciting new edition covering all teachers need to know to confidently teach the computing curriculum as well as explore opportunities for cross-curricular teaching.